THE HISTORY OF THE INTERACTION BETWEEN THE KOKAND KHANATE AND THE HIGHLAND TAJIK BEYKDOMS - Ibraximov Barotjon Botirovich (Scholar Express Journal, 2025)
This article examines the political, economic, and military relations between the Kokand Khanate and the mountainous beyliks of Tajikistan — Hisor, Kulob, Qarotegin, Darvoz, and Baljuvon — during the 18th–19th centuries. The study is based on comparative historical and geopolitical methods. Findings indicate that while the Kokand Khanate failed to establish full control over these regions, it strengthened influence through trade, taxation, and military alliances. The expansion of the Russian Empire and the rise of the Bukhara Emirate eventually terminated these relations
Keywords: Kokand Khanate; Mountainous Tajikistan; Hisor; Kulob